THE CONCEPT OF UNIVERSAL HUMANITY OF PANCASILA BASED ON AL-QUR’AN - Akmal Rizki Gunawan Hasibuan; Rabiyannur Lubis; Abdul Khoir (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This is important to do research of the concepts that offered by Pancasila. Look at about global politics today imposes a variety of ways to achieve the goals, which lead to radicalism and terrorism. Interestingly, the stigma is by the western, the proportion is more closely compared with the Islamic movement, since the incident of 9/11. The data collected from 80 articles, journals and books. The data that were analyzed Madhui al-Farmawi’s theory. The results of this discuss study that the concept of the universal concept of Pancasila based on Al-Quran carrying on the interconnection and harmonious interaction between humans and Allah (habl maa Allah), humans with themselves (habl maa nafsih), and humans with others (habl maa-nas).